Practical synthesis and reactivity of [3]dendralene - Bradford, T.; Payne, Alan; Willis, A.; Paddon-Row, M.; Sherburn, M. (American Chemical Society, 2010)
A convenient and high-yielding three-step synthesis of the simplest branched triene, [3]dendralene, has been devised. The synthesis is robust and operationally simple, requiring no chromatography and involving no protecting groups or specialized equipment, allowing the synthesis of the volatile hydrocarbon in pure, solvent free form on a multigram scale. The stability, dimerization when stored neat, and Diets-Alder reactivity of [3]dendralene-including double cycloaddition sequences and catalytic enantio selective variant-are reported.